The 5Cs of beating the coronavirus outbreak - CHAN, David (Institutional Knowledge at Singapore Management University, 2020)
Practise being calm, cautious, considerate, caring and collectivistic. And use these tools to build up arsenal of psychological defence against the virus threat.